Assessing Safety and Clinical Effectiveness of New Approaches to Planning and Integrated Implementation of Full-Mouth Reconstruction - Dzalaeva, Fatima; Chikunov, Sergey; Utyuzh, Anatoly; Mikhailova, Maria; Budunova, Marzhanat (European Journal of Dentistry, 2020)
Objectives Planning, adequate preparation, and further prosthodontic management are the most important steps in the treatment of this population of patients with dental and mandibular anomalies. The purpose of the article is the improvement of safety and clinical effectiveness of prosthodontic rehabilitation of patients after full-mouth reconstruction.Materials and Methods A single-center open prospective nonrandomized study, examination, and treatment of 198 patients with partial or total absence of teeth were performed. Higher safety and clinical effectiveness of the treatment were found in the patients of the main group who showed a significant reduction in the rate of complications relative to the comparison group. In the main group, the number of aesthetic defects and cases of repeated prosthetics decreased in comparison with the corresponding occurrence rate of such cases in patient groups.Results It showed statistically significantly reduction in the rates of occurrence of the complications when using the proposed algorithm: the rate of inflammation of the marginal periodontium and peri-implant tissues in the main group was 2.9 times less frequent and loosening of the supporting implants was 3.9 times less frequent. The rate of polymer chipping or abrasion in the area of the incisal edge or masticatory surface was two times lower in the main group of patients, short crowns were found 1.9 times less often, sores in the area of the dental pontic in the main group were 1.8 times less frequent than in the comparison group, and no fractures of bridgework were found in the main group. The frequency of neuralgic facial pain in the patients of the main group was 5.2 times less than in the comparison group, complaints about pain in the temporomandibular joint area were 8.4 times less frequent, increased abrasion of antagonist teeth was 3.9 times less frequent, and phonetics disorders were 8.4 times less frequent.The effectiveness of the algorithm developed by us is also confirmed by the fact that the number of aesthetic defects and cases of the need for repeated prosthetic treatment was reduced in comparison with the corresponding frequency of such cases in groups of patients where standard approaches to prosthetics were applied. In particular, aesthetic defects found in the main group of patients were 2.5 times less frequent than in the comparison group, and repeated prosthetics was performed 2.7 times less frequently.Conclusion Application of the developed comprehensive approach to planning of prosthodontic rehabilitation provides for significant reduction in the frequency of complications and aesthetic defects, as well as cases of repeated need for prosthetics.
Keywords: aesthetic defects; clinical effectiveness; complications; patient satisfaction; prosthodontic treatment